Effects of Inonotus obliquus on ameliorating podocyte injury in ORG mice through TNF pathway and prediction of active compounds - Han, Zhaodi; Gong, Le; Xue, Yani; Wang, Rui; Liu, Jing; Wang, Xinyu; Zhao, Wenyan; Liao, Hui; Li, Rongshan (Frontiers in Pharmacology, 2024)
Background: Podocyte injury is a common pathologic mechanism in diabetic kidney disease (DKD) and obesity-related glomerulopathy (ORG). Our previous study confirmed that Inonotus obliquus (IO) improved podocyte injury on DKD rats. The current study explored the pharmacological effects, related mechanisms and possible active components of IO on ORG mice. Methods: Firstly, by combining ultra-high performance liquid chromatography tandem mass spectrometry analysis (UPLC-Q-TOF-MS) with network pharmacology to construct the human protein-protein interaction mechanism and enrich the pathway, which led to discover the crucial mechanism of IO against ORG. Then, ORG mice were established by high-fat diet and biochemical assays, histopathology, and western blot were used to explore the effects of IO on obesity and podocyte injury. Finally, network pharmacology-based findings were confirmed by immunohistochemistry. The compositions of IO absorbed in mice plasma were analyzed by UPLC-Q-TOF-MS and molecular docking was used to predict the possible active compounds. Results: The network pharmacology result suggested that IO alleviated the inflammatory response of ORG by modulating TNF signal. The 20-week in vivo experiment confirmed that IO improved glomerular hypertrophy, podocyte injury under electron microscopy, renal nephrin, synaptopodin, TNF-α and IL-6 expressions with western blotting and immunohistochemical staining. Other indicators of ORG such as body weight, kidney weight, serum total cholesterol, liver triglyceride also improved by IO intervention. The components analysis showed that triterpenoids, including inoterpene F and trametenolic acid, might be the pharmacodynamic basis. Conclusion: The research based on UPLC-Q-TOF-MS analysis, network pharmacology and in vivo experiment suggested that the amelioration of IO on podocyte injury in ORG mice via its modulation on TNF signal. Triterpenoids were predicated as acting components.